Reading Literature: An Ethical Gesture in the Postmodern Context? - Locatelli, Angela (Armenian Folia Anglistika, 2014)
After the so called Ethical Turn in literary theory ethics is still a major issue in literary studies. European Continental philosophy has traditionally been in close touch with ethical issues. Not surprisingly then, it was the influence of French philosophy that, from the Eighties onward, began to put back the ethical in British academic discourse. One of the interesting paradoxes of post-modernity is the fact that, while it promotes an attitude of scepticism, oriented towards a strong suspicion of strong ideologies, it is also an attempt to promote emancipative activities (demonstrated in the Canon Debate, Post-Colonial Studies, Trauma Studies, and a broad Ethical Turn in different sectors of the humanities). This contribution wishes to investigate the issue of ethics and literature in the postmodern context, with reference to contemporary philosophy and literary theory and aims to propose that Postmodern culture still needs complex literature, and (the promotion of) appropriate hermeneutic skills to deal with it.
Keywords: postmodern culture; ethics and politics; representation; dialogic reading of literature